ASSESSMENT OF INDICATORS OF INCREASING THE ECONOMIC EFFICIENCY OF AGROCLUSTERS (Marketing Journal, 2025)
This article provides a detailed assessment and analysis of the indicators for enhancing the efficiency of agrocluster activities. The study examined the volume of agricultural production in the Khorezm region as a key indicator and evaluated its impact on the efficiency of agroclusters on a scientific basis. In addition, supplementary economic and technological indicators, including product quality, labor productivity, resource use efficiency, market share, processing volume, and innovation activity, were analyzed, and practical recommendations for their improvement were developed.
Keywords: agroclusters; efficiency indicators; agricultural products; product quality; labor productivity; innovation activity; market share; processing volume. № 10-SON OKTA BR; 2025 -YIL 267